2013
DOI: 10.1002/14651858.cd007427.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Physical tests for shoulder impingements and local lesions of bursa, tendon or labrum that may accompany impingement

Abstract: There is insufficient evidence upon which to base selection of physical tests for shoulder impingements, and local lesions of bursa, tendon or labrum that may accompany impingement, in primary care. The large body of literature revealed extreme diversity in the performance and interpretation of tests, which hinders synthesis of the evidence and/or clinical applicability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 254 publications
1
63
0
3
Order By: Relevance
“…Special tests are extensively described in the literature 68 but data on diagnostic accuracy of special tests is sparse and inconclusive, thereby leading to heavy reliance on expensive shoulder imaging to aid in the diagnosis 810 . Prior studies have provided data on individual or only few of the special tests described for the rotator cuff 26,27,3035 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Special tests are extensively described in the literature 68 but data on diagnostic accuracy of special tests is sparse and inconclusive, thereby leading to heavy reliance on expensive shoulder imaging to aid in the diagnosis 810 . Prior studies have provided data on individual or only few of the special tests described for the rotator cuff 26,27,3035 .…”
Section: Discussionmentioning
confidence: 99%
“…However, data on the sensitivity and specificity of special tests are sparse and conflicting, providing little guidance to the clinician in the diagnosis of this common musculoskeletal disorder. This issue is highlighted in several recent expert reviews 810 . Thus, there is need for studies assessing diagnostic accuracy of special tests for rotator cuff tears to guide the clinician during their physical examination.…”
Section: Introductionmentioning
confidence: 99%
“…[29] Although some individual studies have reported sensitivity and specificity properties for these maneuvers that may seem reasonable, other studies have arrived at different results, and a recent Cochrane review has not found sufficient evidence to recommend any examination element, likely due to “extreme diversity” in techniques compared to the original descriptions. [30] Many studies have not examined combinations of individual elements into a systematic, synthetic approach; some even question the relevance and role of the physical examination altogether, in contrast with the summary recommendation of the US Bone and Joint Initiative. [31, 32] No group has yet proposed a detailed checklist of elements for the physical exam of the shoulder for use in a multidisciplinary educational program.…”
Section: Discussionmentioning
confidence: 99%
“…68 This procedure was adopted from a published diagnostic test accuracy protocol from the Cochrane Library in the context of physical examination of the shoulder. 27 We performed our electronic literature search in 3 databases (MED-LINE, Embase, Allied and Complementary Medicine Database), consistent with recommendations to search in more than just 1 database for diagnostic test accuracy studies. 16,89 We decided not to search within PEDro, in contrast to authors of other diagnostic test accuracy reviews, 13,78 because this database contains few diagnostic studies.…”
Section: Discussionmentioning
confidence: 99%